TELECARE FOR THE ELDERLY: EFFECTIVENESS OF REMOTE MONITORING OF VITAL SIGNS IN HOME SETTINGS - Aneta Rasińska; Paulina Bala; Justyna Matusik; Piotr Rzyczniok; Mateusz Kopczyński; Justyna Jachimczak (International Journal of Innovative Technologies in Social Science, 2025)
Introduction and Objective: The growing aging population and increased prevalence of chronic diseases necessitate innovative healthcare approaches. Telecare—particularly remote monitoring of vital signs—has emerged as a promising method to support older adults in home environments. This review aims to evaluate the effectiveness of remote monitoring systems in improving health outcomes, safety, and independence among elderly individuals.Review Methods: A narrative review methodology was used to synthesize current evidence from peer-reviewed articles published between 2018 and 2024. Major databases such as PubMed, Scopus, and Google Scholar were searched using targeted keywords. Articles included focused on the use of remote vital sign monitoring technologies in home-based care for individuals aged 60 and above.State of Knowledge: The findings suggest that telecare technologies, including wearable sensors and connected health platforms, contribute to earlier detection of clinical deterioration, reduction in hospital readmissions, and enhanced patient engagement. Furthermore, remote monitoring improves medication adherence and enables continuous communication between patients and healthcare providers. Despite technological and ethical challenges, user satisfaction and acceptance remain generally high when systems are tailored to older users' needs.Conclusion: Telecare with remote vital sign monitoring holds significant potential to support aging in place while reducing healthcare burdens. Integrating these technologies into standard care models can enhance elderly care quality, improve health outcomes, and increase autonomy. Further interdisciplinary research is needed to optimize implementation strategies and address remaining barriers to scalability and equity.